TELAAH STRATEGI PEMBUKTIAN PENUNTUT UMUM DALAM KASUS TINDAK PIDANA NARKOTIKA YANG DIJATUHI HUKUMAN MATI - Dwi Wahyu Septiansyah; Muhammad Rustamaji (Sebelas Maret University, 2025)
This research aims to analyze the public prosecutor’s evidentiary strategy in proving criminal elements and the judge’s legal considerations or ratio decidendi in deciding to impose the death penalty for narcotics crimes in the case of Decision Number 501/Pid.Sus/2020/PN Btm. This research is prescriptive doctrinal legal research. The types of legal materials used are primary and secondary legal materials. The legal material sources used include primary and secondary legal material sources. The technique for collecting legal materials used is literature study from books, statutory regulations and related legal documents. Analysis of legal materials using the deductive syllogism method. Based on the results of the research and discussion, it was found that the public prosecutor’s evidentiary strategy in case Number: 501/Pid.Sus/2020/PN Btm was carried out using several strategies, namely an evidentiary strategy based on evidence presented at trial, an evidentiary strategy based on articles used in the indictment, and the evidentiary strategy uses splitting which results in the maximum verdict, namely the death penalty. The judge’s legal considerations in handing down his decision are based on juridical considerations (Public Prosecutor’s indictment, Defendant’s statement, Witness testimony, Expert testimony, evidence, and articles in criminal law regulations) and non-juridical considerations (background of the Defendant’s actions, consequences the Defendant’s actions, the Defendant’s personal condition, and the Defendant’s religion) in rendering a criminal decision.